Pengaruh Kebijakan Pengurangan Beban Pajak Penghasilan bagi Pembayar Zakat (Studi Kasus Muzakki di Lembaga Amil Zakat YDSF Surabaya) - Muhammad Zaki; Royyan Ramdhani Djayusman (University of Darussalam Gontor, 2016)
Zakat is an obligation for a capable Muslim, while tax is also an obligation borne by every citizen. Meanwhile, zakat and taxes are two instruments that have the same function, which is to perform the income distribution function and overcome the poverty of its citizens. If the Muslim community in Indonesia pays these two obligations completely, then it will add a burden to the Muslim community in Indonesia. Therefore, Muslims in Indonesia who have paid zakat may be subject to a deduction of the tax burden so that Indonesian Muslim societies do not have double burden of obligation in their country. This study aims to determine the difference in the average number of muzakki in Institute Amil Zakat YDSF Surabaya before and after the policy of income tax deduction for paying zakah. Furthermore, the purpose of this study is to know the perception of opinion muzakki about the policy of deduction of income tax burden for zakat payer in YDSF Surabaya. This type of research is field research using triangulation method. The triangulation method is used to reinforce the data under study. And to identify components through quantitative data analysis and then collect qualitative data to expand the available information. The results showed that the average value of muzakki before this policy was 1523.37, while the mean value of muzakki after the policy was 1413.35. The difference indicates that the average amount of muzakki before the policy of reducing the tax burden is greater than the average amount of muzakki after the policy of reducing the tax burden. That is, the number of muzakki in zakat amil institutions decreased after the implementation of the policy of reducing the tax burden for the payers of zakat. The perception of muzakki regarding the existence of this policy is that this policy does not have a significant effect on the tax burden they have, because the amount of tax burden reduced by zakat only slightly.